New Antenna for Detecting Polarization States of Terahertz - Shi, Wei; Wang, Zhiquan; Li, Chaofan; Hou, Lei; Pan, Yue (Frontiers in Physics, 2022)
The polarization measurement of terahertz (THz) waves is indispensable in THz time-domain spectroscopy (THz-TDS) applications to detect material properties. The rapid development of accurate THz wave polarization-sensitive detectors will greatly promote THz-TDS applications. A new type of photoconductive antenna array detector is proposed in this paper. The antenna is composed of two vertical 1*2 arrays, which respectively detect the orthogonal component of the terahertz pulse in any direction, while quickly and accurately detecting the polarized THz waves. Rotating the detector to measure the THz electric field at different angles shows the reliability of the detector for THz wave polarization measurement. Its polarization detection accuracy is 0.2°. At the same time, we use the response matrix to analyze the symmetry of the antenna array.